Ammonia emission from a manure-belt laying hen facility equipped with an external manure drying tunnel. (1st April 2020) - Rosa, E.; Arriaga, H.; Merino, P.
Abstract: Ammonia is the main pollutant associated to laying hen facilities. Best Available Techniques such as manure drying tunnels have been implemented to minimise ammonia losses. However, scarce information is available about their performance as a cleaner technology. Ammonia emission from a manure-belt laying hen building and the annexed external manure drying tunnel were measured from July 2015 to October 2016 under Continental Mediterranean climate conditions. Ammonia emission from the building and manure drying tunnel were continuously measured by a photoacoustic multi gas analyser. Temperature and relative humidity were monitored. The uncertainty of ammonia emission calculation was examined. Nitrogen mass balance was also used to estimate ammonia losses from the building. Results showed that the annual mean ammonia emission from the building was 93.8 mg ammonia d −1 hen −1 . Mean ammonia emission uncertainty in the building was 9.7% throughout the sampling period. Ventilation rate was identified as the main factor affecting uncertainty due to the variability of fans operation. Concerning the manure drying tunnel, mean ammonia emission was 209.3 mg NH3 d −1 hen −1 . Ammonia losses were affected by the atmospheric temperature and relative humidity, and manure dry matter content in both systems. Manure ammonia emission should be researched in following steps of the manure continuum to state the manure drying tunnel as a cleaner production technology. Ammonia emission estimation by nitrogen mass balance method was 98.4 mg NH3 d −1 hen −1 . It was demonstrated to be a good indicator of the ammonia emission over the year although it did not reflect the variations between shorter time periods. Highlights: Annual mean ammonia emission from the building and manure drying tunnel were 93.8 and 209.3 mg NH3 d −1 hen −1, respectively. Interactions of temperature, relative humidity and manure dry matter content affected ammonia emissions. Nitrogen mass balance estimation was a good indicator of the ammonia emission from the building.